2019
DOI: 10.1002/hsr2.136
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura patients' attitudes toward depression management: A qualitative study

Abstract: Background and aims Thrombotic thrombocytopenic purpura (TTP) is a rare disorder characterized by acute episodes of systemic microvascular thrombosis; TTP is more common in adults, women, and African‐Americans (Blacks). Our Oklahoma TTP Registry documented that survivors have an increased prevalence of depression compared with the general population; however, many patients' depression remains untreated. Moreover, studies identifying attitudes toward depression management are lacking. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“…Overall, our survey participants met HADS criteria for moderate anxiety and depression, with scores comparable to previous studies in other diseases considered to be similar to iTTP in symptomology (Guillain-Barré syndrome, stroke or sepsis) [32,33]. Evidence suggests that the prevalence of depression among adults with iTTP is much higher than healthy controls [26,31] and European and US population norms [10,15,26,30], after controlling for certain demographics. Alwan et al, also showed that self-reported depression and anxiety existed regardless of neurological symptoms [29].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Overall, our survey participants met HADS criteria for moderate anxiety and depression, with scores comparable to previous studies in other diseases considered to be similar to iTTP in symptomology (Guillain-Barré syndrome, stroke or sepsis) [32,33]. Evidence suggests that the prevalence of depression among adults with iTTP is much higher than healthy controls [26,31] and European and US population norms [10,15,26,30], after controlling for certain demographics. Alwan et al, also showed that self-reported depression and anxiety existed regardless of neurological symptoms [29].…”
Section: Discussionsupporting
confidence: 80%
“…The majority of survey participants reported frequent interference in family, social life, and work. These findings add to previous qualitative research illustrating the inter-relationships between HRQoL concepts; participants described how the inability to do normal activities and socialize led to isolation and feelings of worthlessness, and fear of infection from others led people to self-isolate [31].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The prevalence of major depression in our iTTP patients was 21.6% and 34.5% for 2015 and 2016, respectively, far above the prevalence in our population controls (4.6%) and the reported 12-month prevalence in the German population (9.3%) [ 28 ]. These results are consistent with our previous findings [ 10 ] and with other studies showing a significantly increased point prevalence of depression from 19% up to 65% in iTTP survivors [ 6 , 8 , 9 , 29 , 30 ]. A strong association between chronic physical illness and depression has been reported [ 15 , 31 ].…”
Section: Discussionsupporting
confidence: 94%